Literaturkontakte Ugarits (Münster)
251 sayfa
Keywords: “Using the example of Ugarit, the contributions show the transregional relationships of a North-Syrian metropolis in the 2nd half of the 2nd millennium BC, which concerned not only the economic level, but also testify to an exchange on a cultural and religious level, in which different languages and traditions were not dividing but could stimulate one another. In addition to the many important individual aspects that the contributions deal with (in addition to mythical-epic traditions, the areas of wisdom and administration), the volume also sheds light on the exciting question of the relationship between local and transregional traditions, as they are particularly evident in the legacy of the elites of the time” --